2019
DOI: 10.1111/gcb.14637
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of gradual size‐dependent shifts in body size and growth of fish in response to warming

Abstract: A challenge facing ecologists trying to predict responses to climate change is the few recent analogous conditions to use for comparison. For example, negative relationships between ectotherm body size and temperature are common both across natural thermal gradients and in small‐scale experiments. However, it is unknown if short‐term body size responses are representative of long‐term responses. Moreover, to understand population responses to warming, we must recognize that individual responses to temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(135 citation statements)
references
References 67 publications
(134 reference statements)
8
117
4
1
Order By: Relevance
“…Such reduction in body size is consistent with the temperature-size-rule (TSR) (i.e. body size decrease at higher temperature) (Atkinson 1994;Kingsolver and Huey 2008;Ohlberger 2013;Horne et al 2017;Huss et al 2019) and is particularly evident in aquatic environments (Forster et al 2012;Horne et al 2015), where fish and other aquatic organisms' average body size has already declined by 5-20% over the last two decades (Baudron et al 2014;Audzijonyte et al 2016;van Rijn et al 2017). Experimental temperature-size responses, models and meta-analyses suggests that body size will further reduce by 3-5% per degree of warming in aquatic arthropods, while in fishes it may decline by 14-24% by 2050 under a higher green-house gases emission scenario (A2 scenario, IPCC 2007;Cheung et al 2013;Pauly and Cheung 2018a).…”
Section: Introductionsupporting
confidence: 60%
“…Such reduction in body size is consistent with the temperature-size-rule (TSR) (i.e. body size decrease at higher temperature) (Atkinson 1994;Kingsolver and Huey 2008;Ohlberger 2013;Horne et al 2017;Huss et al 2019) and is particularly evident in aquatic environments (Forster et al 2012;Horne et al 2015), where fish and other aquatic organisms' average body size has already declined by 5-20% over the last two decades (Baudron et al 2014;Audzijonyte et al 2016;van Rijn et al 2017). Experimental temperature-size responses, models and meta-analyses suggests that body size will further reduce by 3-5% per degree of warming in aquatic arthropods, while in fishes it may decline by 14-24% by 2050 under a higher green-house gases emission scenario (A2 scenario, IPCC 2007;Cheung et al 2013;Pauly and Cheung 2018a).…”
Section: Introductionsupporting
confidence: 60%
“…Such population-level metrics vary not only with individual growth but also with mortality, and can therefore not be used to infer warming effects on body growth. The variation in body growth responses to high temperatures over ontogeny observed in fishes in natural systems [4] as well as experimentally in unfished populations over long time scales ( [7], figure 2b) is associated with larger size at young ages ( [4,7]; figure 2c), but no [4] or smaller [7] increases in size at older age (figure 2c). Responses to temperature differences occurring across generations may differ from plastic responses of individuals arising from changes in temperature-and sizedependent physiological and ecological processes, owing to evolutionary adaptation.…”
Section: (B) Faster Body Growth Rate Of Small But Not Large Individualsmentioning
confidence: 87%
“…Responses to temperature differences occurring across generations may differ from plastic responses of individuals arising from changes in temperature-and sizedependent physiological and ecological processes, owing to evolutionary adaptation. For example, Huss et al [7] found that warming also resulted in gradually faster growth of small individuals over more than 10 generations (figure 2b), suggesting that evolutionary adaptations to warming may need to be accounted for. Alternatively, the longer growth season or effects on resource availability caused by warming may enable small individuals to grow faster as well as large individuals to maintain growth, and hence increase in size at age owing to fast growth when young.…”
Section: (B) Faster Body Growth Rate Of Small But Not Large Individualsmentioning
confidence: 99%
“…Moreover, using populations exposed to contrasting thermal habitats for many generations allowed us to examine long‐term responses to elevated temperatures (Huss, Lindmark, Jacobson, van Dorst, & Gårdmark, ). This avoids the limitations of short‐term laboratory experiments that expose animals to high temperature for only one or a few generations.…”
Section: Discussionmentioning
confidence: 99%